Innovations for community services : 17th International Conference, I4CS 2017, Darmstadt, Germany, June 26-28, 2017, Proceedings /: 17th International Conference, I4CS 2017, Darmstadt, Germany, June 26-28, 2017, Proceedings. (2017) - Unknown
No abstract available